A New Cold-Adapted and Salt-Tolerant Glutathione Reductase from Antarctic Psychrophilic Bacterium Psychrobacter sp. and Its Resistance to Oxidation - Yatong Wang; Quanfu Wang; Yanhua Hou (International Journal of Molecular Sciences, 2020)
A new glutathione reductase gene (psgr) coding for glutathione reductase (GR) from an Antarctic bacterium was cloned and overexpressed into Escherichia coli (E. coli). A sequence analysis revealed that PsGR is a protein consisting of 451 amino acids, and homology modeling demonstrated that PsGR has fewer hydrogen bonds and salt bridges, which might lead to improved conformational flexibility at low temperatures. PsGR possesses the flavin adenine dinucleotide (FAD) and nicotinamide adenine dinucleotide phosphate (NADPH) binding motifs. Recombinant PsGR (rPsGR) was purified using Ni-NTA affinity chromatography and was found to have a molecular mass of approximately 53.5 kDa. rPsGR was found to be optimally active at 25 °C and a pH of 7.5. It was found to be a cold-adapted enzyme, with approximately 42% of its optimal activity remaining at 0 °C. Moreover, rPsGR was most active in 1.0 M NaCl and 62.5% of its full activity remained in 3.0 M NaCl, demonstrating its high salt tolerance. Furthermore, rPsGR was found to have a higher substrate affinity for NADPH than for GSSG (oxidized glutathione). rPsGR provided protection against peroxide (H2O2)-induced oxidative stress in recombinant cells, and displayed potential application as an antioxidant protein. The results of the present study provide a sound basis for the study of the structural characteristics and catalytic characterization of cold-adapted GR.